Effect of Tongqiao Huoxue Decoction on cAMP-PKA Signaling Pathway in Rats with Vascular Dementia - Yufen WU; Changjun LU; Linglu DUN; Xiaocui LEI; Yuqiao QIN; Guocheng LIU; Bingxin WEI (康复学报, 2016)
Objective:To investigate the effects of Tongqiao Huoxue decoction on expression levels of cyclic adenosine monophosphate (cAMP) and protein kinase A (PKA) in rats with vascular dementia (VD).Methods:The rats were randomly divided into sham operation group, VD model group, the large, middle and small dose Tongqiao Huoxue treatment groups. The rat model of VD was built by intermittently clipping common carotid artery. Morris water maze test determined whether the surgery had been successful. After that rats were perfused with Tongqiao Huoxue decoction, and the changes of cAMP and PKA were detected by Enzyme-linked immunosorbent assay (ELISA).Results:The content of cAMP and PKA in VD rats were lower than those in sham operated rats (P<0.01). The above indexes of the large-and middle-dose Tongqiao Huoxue groups were higher compared with the VD model group (P<0.01).Conclusion:Tongqiao Huoxue decoction increases the content of cAMP and PKA, and thus strengthens the expression of cAMP-PKA.